Swedish youth football players' attitudes towards moral decision in sport as predicted by the parent-initiated motivational climate. (July 2016) - Wagnsson, Stefan; Stenling, Andreas; Gustafsson, Henrik; Augustsson, Christian
Abstract: Objectives: The purpose of this study was to examine associations between late adolescent football players' perceptions of the motivational climate – as initiated by mothers and fathers – and attitudes towards moral decision making in sports. Design: Cross-sectional. Methods: Participants were 213 Swedish football players (144 males, 67 females) aged 16–19 years who completed measures assessing perceived parent-initiated motivational climate (i.e., success-without-effort climate [SWEC]; worry conducive climate [WCC]; and learning/enjoyment climate [LEC]) and attitudes towards moral decision-making in sport (i.e., acceptance of cheating [AOC]; acceptance of gamesmanship [AOG] and keeping winning in proportion [KWIP]). Results: Canonical correlations demonstrated moderate positive relations between parent-initiated − both mother and father − performance climates (WCC and SWEC) and AOC and AOG. Moreover, the relationship between mother and father-initiated learning/enjoyment climate (LEC) were shown to be moderately and positively associated with the prosocial attitude dimension of KWIP. Results also showed that a mother-initiated LEC and a mother-initiated SWEC were stronger predictors of the criterion variables (AOC, AOG, and KWIP) than equivalent father-initiated climate dimensions. Conclusions: The results highlight the importance of considering the relationship between parent-initiated climates − especially initiated by mothers − and the development of moral decision-making among youth football players. Highlights: Parent motivational climate are related to youth football players' moral attitudes. A mother-initiated climate are stronger related to players' moral attitudes. Mothers should be encouraged to down-play the importance of winning.